Manfaat Penerapan Sistem Manajemen Kualitas ISO 9000:2000 dalam Lingkungan Bisnis di Indonesia - Shanti, . (Jurnal Widya Manajemen & Akuntansi, 2002)
This article used to get deeper understanding of the business value of ISO 9000:2000 in Indonesia. The strongest reasons of implementing ISO 9000:2000 in Indonesia companies is to improve their quality systems to be more focus and systematic . The business value of implementing ISO 9000:2000 in Indonesia plants are enhancing systematic system, improving customer confidence, improving work efficiency, improving intern, communication, increasing employees awareness, reducing customer complaint, improving product quality and competition tools. The future direction of quality system in Indonesia companies indicate that the usage standard of integrating system, integrating quality, environment and safety system will be growth rapidly.